Water and carbohydrate ingestion during prolonged exercise increase maximal neuromuscular power - Fritzsche, R. G.; Switzer, T. W.; Hodgkinson, B. J.; Lee, S. H.; Martin, J. C.; Coyle, E. F. (Journal of Applied Physiology, 2000)
This study investigated the individual and combined effects of water and carbohydrate ingestion during prolonged cycling on maximal neuromuscular power (Pmax), thermoregulation, cardiovascular function, and metabolism. Eight endurance-trained cyclists exercised for 122 min at 62% maximal oxygen uptake in a 35°C environment (50% relative humidity, 2 m/s fan speed). Pmax was measured in triplicate during 6-min periods beginning at 26, 56, 86, and 116 min. On four different occasions, immediately before and during exercise, subjects ingested 1) 3.28 ± 0.21 liters of water with no carbohydrate (W); 2) 3.39 ± 0.23 liters of a solution containing 204 ± 14 g of carbohydrate (W+C); 3) 204 ± 14 g of carbohydrate in only 0.49 ± 0.03 liter of solution (C); and 4) 0.37 ± 0.02 liter of water with no carbohydrate (placebo; Pl). These treatments were randomized, disguised, and presented double blind. At 26 min of exercise, Pmax was similar in all trials. From 26 to 116 min, Pmax declined 15.2 ± 3.3 and 14.5 ± 2.1% during C and Pl, respectively; 10.4 ± 1.9% during W (W > C, W > Pl; P < 0.05); and 7.4 ± 2.2% during W+C (W+C > W, W+C > C, and W+C > Pl; P < 0.05). As an interesting secondary findings, we also observed that carbohydrate ingestion increased heat production, final core temperature, and whole body sweating rate. We conclude that, during prolonged moderate-intensity exercise in a warm environment, ingestion of W attenuates the decline in Pmax. Furthermore, ingestion of W+C attenuates the decline in maximal power more than does W alone, and ingestion of C alone does not attenuate the decline in Pmax compared with Pl.